Bioremediation of antimony from wastewater by sulfate-reducing bacteria: Effect of the coexisting ferrous ion. (March 2020) - Xi, Yanni; Lan, Shiming; Li, Xin; Wu, Yangtao; Yuan, Xingzhong; Zhang, Chang; Yunguo, Liu; Huang, Yicai; Quan, Bangyu; Wu, Shaohua
Abstract: Metal sulfide precipitation by sulfate-reducing bacteria (SRB) is considered to be a promising method for antimony (Sb) removal from wastewater. Moreover, the addition of ferrous ions (Fe(II)) to the SRB system is expected to increase the metabolic activity of SRB. In this study, batch microcosms of SRB, with 0–600 mg/L Fe(II), are used to assess the effect of Fe(II) on enzyme activity, Sb bioremediation process, and antioxidant capacity of precipitates. Especially, the presence of 100–200 mg/L of Fe(II) enhanced the hydrogenase activity of the microcosms and accelerated the consumption of sulfate and bioprecipitation of Sb(III), thereby increasing the efficiency of total Sb removal. In the first three days, the SRB system with 200 mg/L Fe(II) displayed the highest Sb(V) removal ratio, whereas, the SRB system with 100 mg/L Fe(II) displayed the highest Sb(V) removal ratio (98.3%) after 9-days of incubation. Characterisation of the precipitate revealed that the soluble Sb(V) was mainly converted to Sb2 S3 and Sb2 O3, and the presence of Fe(II) prevented Sb2 S3 from being oxidized by air. Graphical abstract: Image 1 Highlights: The adaptive phase of SRB could effectively be shorten by Fe(II). Adding Fe(II) can increase the hydrogenase activity of SRB, thereby accelerating the Sb bioprecipitation. Adding Fe(II) could quickly stabilize the pH of the SRB system. Sb(V) removed by SRB was mainly converted to Sb2 S3 and Sb2 O3 . The presence of Fe(II) could prevent the Sb2 S3 from being oxidized by air.